Effect of phytase supplementation on plasma and organ myo-inositol content and erythrocyte inositol phosphates as pertaining to breast meat quality issues in chickens - H. Whitfield; C. Laurendon; S.J. Rochell; S. Dridi; S.A. Lee; T. Dale; T. York; I. Kuehn; M.R. Bedford; C.A Brearley (Journal of Applied Animal Nutrition, 2022)
‘Woody breast’ (WB) and ‘white striping’ in broiler meat is a global problem. With unknown etiology, WB negatively impacts bird health, welfare and is a significant economic burden to the poultry industry. New evidence has shown that WB is associated with dysregulation in systemic and breast muscle-oxygen homeostasis, resulting in hypoxia and anaemia. However, it has been observed that phytase (Quantum Blue (QB) a modified, E. coli-derived 6-phytase) super dosing can reverse dysregulation of muscle-oxygen homeostasis and reduces WB severity by ~5%. The objective of this study was to assess whether levels of Ins(1,3,4,5,6)P5, the main allosteric regulator of haemoglobin, are influenced by changes in plasma myo-inositol arising from super dosing with phytase. To enable this, methods suitable for measurement of myo-inositol in tissues and inositol phosphates in blood were developed. Data were collected from independent trials, including male Ross 308 broilers fed low and adequate calcium/available phosphate (Ca/AvP) diets supplemented with QB at 1,500 phytase units (FTU)/kg, which simultaneously decreased gizzard InsP6 (P<0.001) and increased gizzard myo-inositol (P<0.001). Similarly, male Cobb 500 broiler chicks fed a negative control (NC) diet deficient in AvP, Ca and sodium or diet supplemented with the QB phytase at 500, 1000 or 2,000 FTU/kg increased plasma (P<0.001) and liver (P=0.007) myo-inositol of 18d-old birds at 2,000 FTU/kg. Finally, QB supplementation of Cobb 500 breeder flock diet at 1,250 FTU/kg increased blood myo-inositol (P<0.001) and erythrocyte Ins(1,3,4,5,6)P5 (P=0.011) of their 1d-old hatchlings. These data confirmed the ability of phytase to modulate inositol phosphate pathways by provision of metabolic precursors of important signalling molecules. The ameliorations of WB afforded by super doses of phytase may include modulation of hypoxia pathways that also involve inositol signalling molecules. Elevations of erythrocyte Ins(1,3,4,5,6)P5 by phytase supplementation may enhance systemic oxygen carrying capacity, an important factor in the amelioration of WB and WS myopathy.